Influence Of Fashion Trend And Promotion On The Purchase Decisions (Survey of Sheika Hijab Shop Consumers) - Gita Khoerunnisa; Budhi Wahyu Fitriadi; Dudu Risana (Journal of Indonesian Management, 2023)
This study aims to determine the effect of fashion trends and promotions simultaneously on purchasing decisions at Sheika Hijab Stores. The influence of fashion trends and promotions partially on purchasing decisions at the Sheika Hijab Store. The method used in this research is analytical descriptive with a quantitative approach. With a research sample of 100 people as respondents to the Sheika Hijab Shop. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. Based on data that has fulfilled the validity test, reliability test and classic assumption test are processed to produce the regression equation as follows: Y = 1750.862 + 0.527 X1 + 0.436 X2. Simultaneously fashion trends and promotions have a significant effect on purchasing decisions with an fcount of 273.244 and a significance level of 0.000. From the calculation of the coefficient of determination, the R Square value is 0.849 or 84.9%. shows the influence of fashion trends and promotions on purchasing decisions and the remaining 15.1% is the influence of other variables outside the variables used in this study. Partially the fashion trend variable has a significant effect on purchasing decisions, as well as the promotion variable partially having a significant effect on purchasing decisions.